Application of metabolic phase-specific modified nutrition risk in critically ill score: a prospective observational study in critically ill patients - Lee, Geon Ho; Kim, Ye Ju; Park, So Hyang; Park, Sunny; Lim, Sung Yoon; Choi, Soo An (Frontiers in Nutrition, 2024)
Background and aims The prevalence of malnutrition in intensive care units (ICU) is high and can be caused by poor intake or absorption of nutrients in the digestive track, as well as disease-related inflammation. As strong catabolism restricts nutrient supply and potentially leads to subsequent malnutrition, appropriate nutrition should be provided based on the metabolic status. However, nutritional support strategies for considering the metabolic phase are not well established. Therefore, this study aimed to establish a strategy for nutritional support in each phase by implementing a phase-specific modified Nutrition Risk in Critically Ill (mNUTRIC) score. Methods This prospective observational study was conducted on all adult patients admitted to the medical ICU for at least 36 h at Seoul National University Bundang Hospital between September 2020 and September 2022. Patient nutrition assessment (mNUTRIC score), clinical information, and nutritional supply (calories and proteins) were measured twice, in the acute phase (measured at 2 days) and late phase (measured at 7 days). The relationship between nutritional supply and 28-day mortality was analyzed using multiple logistic regression according to the mNUTRIC score in the acute and late phases. Risk factors related to 28-day mortality were analyzed using univariate and multivariate Cox proportional hazards regressions. Results Of the 631 patients admitted to the ICU during the study period, 613 were included in the acute phase and 361 patients were included in the late phase. Nutritional supply was associated with 28-day mortality, with high mNUTRIC scores in both the acute and late phases. Cox proportional hazards regression analysis demonstrated that a high mNUTRIC score [hazard ratio (HR) 3.20 and 2.52, respectively], lactate >2.5 mg/dL were independent risk factors in both the acute and late phases. In addition, Albumin <2.5 mg/dL, the presence of neoplasm, and the need for dialysis in the acute phase, calorie adequacy <0.7 in the late phase (HR, 2.19) were identified as additional risk factors. Conclusion The mNUTRIC score is a suitable tool for identifying critically ill patients who benefit from nutritional support. Nutritional supply should be considered for patients with high mNUTRIC scores in both the acute and late phases; however, careful supply should be provided in the acute phase and sufficient supply should be provided in the late phase.